Dampak Modal Sosial, Digitalisasi Bisnis, Dan Pemanfaatan Teknologi Terhadap Keberlangsungan UMKM Di Kabupaten Malang - Finadila Arifin; Jeni Susyanti; Muhammad Agus Salim (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This research was conducted in Malang Regency. The type of research used is explanatory research with a quantitative approach. The purpose of this study was to determine the effect of social capital, business digitalization and technology utilization on the sustainability of SMEs. The independent variables used are social capital, business digitalization and technology utilization, while the dependent variable is the sustainability of SMEs. The sample used in this study was 70 respondents from MSMEs in Malang district. Data collection techniques using a questionnaire. The analytical method used is instrument test, path analysis, determination t test using IBM SPSS computer software for data processing. The results of this study indicate that social capital, business digitization and technology utilization have a direct effect on the sustainability of SMEs. Keywords: Social Capital, Business Digitalization, Technology Utilization, MSMEs Sustainability